Determinants of the Sharing Economy Emergence; an experimental study - Dahy, Adham Mohamed Wahied (2016)
This thesis explores the emergence of the newest type of economy the sharing economy one of the fastest growing economic phenomena in contemporary times. This thesis cites numerous research papers that encompass the sharing economy alongside other papers in different fields such as marketing and experimental economics. The main goal of this thesis is to disentangle possible channels that may have led to the increase in use of the sharing economy-provided services. To do so, we conducted an experiment using tools provided by the field of experimental economics. In the theoretical part of this thesis the main aim was to broadly explain what the sharing economy is as well as introduce the concepts to be used in the practical part. At the beginning I focus on defining the sharing-economy concept including its many definitions when it first appeared and the three phases that account for its emergence. I then explain the sharing economy concept providing the reason it is gaining worldwide recognition as well the main enablers behind it major companies involved with it the three main systems operating within it and the economics behind it. Finally I explain the many angles associated with its success, such as the concepts of Web 2.0 and P2P. Towards the end of the theoretical part I introduce the concepts that are relevant to the practical part and the experiment including risk-preferences information cascades and peerpressure. The practical part of this thesis focuses on the experiment including methodology designs treatments results etc. In the practical I present the hypothesis and the econometric model used for running the regression in order to test my hypothesis. Lastly I present the outputs I have obtained after running the regression, and comment on their significance and relevance to my hypothesis.